2019
DOI: 10.3390/agriculture9120254
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Causality of Temperature and Precipitation on Italian Ryegrass (Lolium Multiflorum Lam.) Yield between Cultivation Fields via Multi-Group Structural Equation Model Analysis in the Republic of Korea

Abstract: This study aimed to compare the causality of climatic factors affecting the yield of Italian ryegrass (IRG) between upland fields and paddy fields, by multi-group structure equation modeling. The raw data (n = 728) on forage contains both yield, field type, and the plantation address were collected from the Rural Development Administration, Republic of Korea. The climatic factors were: growing days, temperature and precipitation-in autumn and next spring seasons-from the climate big data of the weather informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…During the study period, the highest yield increase was obtained after the application of N 50 for mixtures LB + TR and LM + TR (50 : 50) -3.00-3.43 t/ha, in relation to the plots fertilised with N 30 . The mean DM yield was higher in the 1 st year of the study, compared to the 2 nd year in all the fertilisation treatments and types of (Kim and Sung 2019). Meteorological data for 2016-2017 showed that both average annual and the growing season temperatures were favourable for the yield.…”
Section: Resultsmentioning
confidence: 84%
“…During the study period, the highest yield increase was obtained after the application of N 50 for mixtures LB + TR and LM + TR (50 : 50) -3.00-3.43 t/ha, in relation to the plots fertilised with N 30 . The mean DM yield was higher in the 1 st year of the study, compared to the 2 nd year in all the fertilisation treatments and types of (Kim and Sung 2019). Meteorological data for 2016-2017 showed that both average annual and the growing season temperatures were favourable for the yield.…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, for the low yields in the southern inland region, it was concluded that other factors, such as soil physical properties and cultivation management for wintering, also contributed to the survival of IRG. According to Kim and Sung [ 18 ], IRG yield in paddy fields was lower than in upland fields due to the short growing period by the rice-IRG rotation system. Therefore, climate is the most important factor, but other factors in the severe cold below zero also affected the yield difference.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ko et al [ 24 ], the southern Korean Peninsula was divided into five regions by temperature distribution: northern inland, central inland, southern inland, coastal, and mountainous regions. In this study, the central inland, southern inland and coastal regions were selected because the northern inland and mountainous regions were not suitable for IRG cultivation [ 18 ]. Suwon (latitude: 37° 25′ N, longitude: 126° 98′ E, n = 321), Jeonju (latitude: 35° 84′ N, longitude: 127° 12′ E, n = 107) and Jeju (latitude: 33° 51′ N, longitude: 126° 53′ E, n = 135) were selected as representative locations for the central inland, southern inland and southern coastal regions, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the indirect effects of precipitation, temperature and soil properties were notable in the paddy fields [ 17 ]. Additionally, when comparing climatic causality between paddy fields and upland fields, the production of Italian ryegrass in the paddy fields was sensitive to temperature due to the short growing period caused by the rice-winter crop rotation system [ 18 ]. Studies on the causal relationship between climate and crop production were also carried out for forage barley [ 19 ] and forage rye [ 20 ].…”
Section: Introductionmentioning
confidence: 99%